Melasma: A Step-by-Step Approach Towards a Multimodal Combination Therapy - Philipp-Dormston WG (Dove Medical Press, 2024)
Wolfgang G Philipp-Dormston1,2 1Hautzentrum Köln/Cologne Dermatology, Cologne, Germany; 2Faculty of Health, University of Witten/Herdecke, Witten, GermanyCorrespondence: Wolfgang G Philipp-Dormston, Hautzentrum Köln/Cologne Dermatology, Schillingsrotter Str. 39-41, Cologne, 50996, Germany, Tel +49 221 39800 200, Fax +49-221-39800 201, Email wpd@haut-zentrum.comAbstract: Melasma is a common challenge in the field of pigmentary skin disorders, exerting a significant emotional and psychosocial burden on patients. The persistent and recurring nature of melasma complicates its management in routine clinical practice. This comprehensive review outlines a stepwise, practical approach encompassing diagnostic, preventive and therapeutic strategies for the management of melasma. A thorough exploration of aggravating and exacerbating factors, including sun exposure, hormonal imbalances, photosensitizing medication and cosmetics, is essential for a holistic assessment of the disease. With an emphasis on consistent and effective photoprotection, initial topical treatment modalities target the melanin production and/or the transfer of melanosomes to keratinocytes. Topical tyrosine inhibitors emerge as the first choice for reducing and preventing hyperpigmentation, with compounds such as thiamidol or tranexamic acid (TXA) being preferred for their safety profile over hydroquinone (HQ), kojic acid and arbutin. Combination with chemical peels can further enhance the therapeutic efficacy, even in cases with resistant melasma. In more severe cases, laser- and light-based interventions may be considered, but with the caveat of the likelihood of recurrence within 3- 6 months. Assisted TXA delivery, via either fractional non-ablative laser or microneedling techniques, can further improve clinical outcomes. In conclusion, an optimal melasma management strategy is a multimodal approach, which includes effective photoprotection and a mix of different topical treatments targeting melanin synthesis, the anti-inflammatory environment, senescence and vascularity. Complementary procedures, such as chemical peels, and laser, light-based or microneedling procedures, with or without TXA, can further expedite melanin clearance in more severely affected instances. Individual discussions with patients regarding treatment expectations, recurrence likelihood and potential side effects are paramount to a comprehensive and successful therapeutic journey.Keywords: melasma, chloasma, hyperpigmentation, melanosis